A Study On The Method Of Teaching English To The First YearStudent Of Smk Muhammadiyah 3 Surakarta In 2011/2012 Academic Year - LESTARI , WINDA DWI (2012)
The subject of this descriptive research is the first year of SMK Muhammadiyah 3 Surakarta in 2011/2012 academic year. The objectives of this research are to describe the teaching method implemented by the English teacher in SMK Muhammadiyah 3 Surakarta and classify the problem faced by the teacher in implementing the method. The writer uses descriptive research. The writer collects the data of this research from teaching-learning process, interview with the teacher, document, and observation. The documents of this research as a report are material, handbook, syllabus, and classroom procedure. Interview in this research is the English teacher of SMK Muhammadiyah 3 Surakarta. The result of this research shows that are: (1) The methods of teaching English implemented by the teacher are: Communicative Language Teaching (CLT), Community Language Learning (CLL), and Cooperative Language Learning (Coop. LL), (2) The problem faced by the teacher in implemented the method is student's lack speaking abilities in English and limited time in Communicative Language Teaching method, too many students in Community Language Teaching method and low motivation of the students also different capabilities of the students in Cooperative Language Learning method.